How "social" is Social TV? The influence of social motives and expected outcomes on the usage of Social TV applications. (October 2015) - Krämer, Nicole C.; Winter, Stephan; Benninghoff, Brenda; Gallus, Christine
Highlights: The study analyzes the predictors of Social TV usage via different platforms. Social TV usage is spurred by the motive to communicate and the expectation of enjoyment and social gratification. Besides Twitter, instant messaging systems emerge as important Social TV platforms. WhatsApp usage to communicate about TV content can be predicted by users' need to belong. We argue that Social TV is predominantly used to fulfill needs of relatedness. Abstract: Social TV applications have become increasingly popular. Building on first results on motives for usage, we aim to provide a comprehensive overview of factors that influence the likelihood of using Social TV applications. Based on theoretical approaches which consider the need to belong to be a fundamental human motivation, a special focus lay on identifying the relative impact of social variables such as social motives as well as expected social outcomes in the sense of social gratifications. An online survey of Social TV users ( N = 101) demonstrated that the general frequency of Social TV usage is predicted by the motives to communicate with others, to gather information and to be entertained as well as the perceived social gratification of increased enjoyment, while there was no significant influence of demographic variables and personality aspects such as extraversion and need to belong. When predicting usage frequency of specific platforms such as Twitter and WhatsApp, however, different patterns emerge: While Twitter usage is influenced by the motive to receive information and to communicate, WhatsApp usage is predicted first and foremost by the need to belong. These results underline the need to differentiate between different platforms and facets of Social TV and highlight the importance of social variables and expected gratifications, which extends prior work on general motives. In terms of practical implications the results suggest that Social TV providers should more carefully cater for the diverging goals of obtaining social and informational gains.